2009
DOI: 10.1530/eje-08-0673
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokine and ghrelin levels in relation to bone mineral density in physically active older women: longitudinal associations

Abstract: Purpose: We investigated the relationship between the decrease in bone mineral mass (BMC) and bone mineral density (BMD) values with baseline adipocytokine and ghrelin concentrations in physically active postmenopausal women. Methods: Leptin, adiponectin, ghrelin, BMC, BMD and different body composition values were measured in 35 women (age: 69.7G6.0 years) before and after a 12-month prospective study period. Results: Significant (P!0.05) decreases in fat-free mass (FFM) (by 2.56%) and BMC (by 1.63%) and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
2
28
0
3
Order By: Relevance
“…A number of clinical studies reported the inverse association of adiponectin and BMD in women [4,[17][18][19]45]. In a longitudinal study, baseline fat mass and adiponectin were associated with decreases in total bone mineral mass in older women [46]. In the Rancho Bernardo Study, adiponectin was inversely associated with BMD at the femoral neck, total hip, lumbar spine, and midshaft radius after 4.4 years and at the femoral neck and total hip almost 9 years later in postmenopausal women [47].…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical studies reported the inverse association of adiponectin and BMD in women [4,[17][18][19]45]. In a longitudinal study, baseline fat mass and adiponectin were associated with decreases in total bone mineral mass in older women [46]. In the Rancho Bernardo Study, adiponectin was inversely associated with BMD at the femoral neck, total hip, lumbar spine, and midshaft radius after 4.4 years and at the femoral neck and total hip almost 9 years later in postmenopausal women [47].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin is known to regulate insulin sensitivity, and low level of this adipocyte-producing hormone has been associated with the progression of diabetes. In addition, high adiponectin levels have been linked to lower BMD [38, 44, 45] and greater BMD loss [46, 47], and its role in stimulating the receptor activator of nuclear factor- κB ligand (RANKL) pathway and inhibiting the production of the decoy receptor for RANKL and osteoprotegerin may contribute greatly to this observation [48]. With the potential interplay of leptin, adiponectin and insulin with bone and type 2 diabetes, we further tested the effect of these factors on the observed difference in BMF content among diabetic and non-diabetic men.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin stimulates osteoblast-receptors to increase osteoblastogenesis and indirectly inhibit osteoclastogenesis [42]. However, higher adiponectin levels are associated with greater bone loss at the lumbar spine in a 12 months longitudinal study conducted in physically active older women [43]. Furthermore, in the Health Aging and Body Composition Study, serum adiponectin was significantly higher in overweight women with fractures compared to women without fractures [40], indicating that adiponectin may be a biomarker of fracture risk [34, 40,41].…”
Section: Factors Affecting Bone Cell Fate In Obesitymentioning
confidence: 99%